Flux vacua in type IIB compactifications on orbifolds: their finiteness and minimal string coupling - Ignatios Antoniadis; Anthony Guillen; Osmin Lacombe (Journal of High Energy Physics)
Abstract We perform a detailed study of (supersymmetric) moduli stabilisation in type IIB toroidal orientifolds with fluxes. We provide strong evidence towards exhaustion of the finite number of inequivalent vacua for a given total 3-form flux charge N flux. We also find that the minimal value of the string coupling g s is given in terms of N flux and present strong evidence for the asymptotic relation g s, min ∼ c / N flux α $$ c/N_{flux}^{α } $$ , with α = 1, 2, valid for not too small N flux, where c is an order 1 coefficient and α depends on the orbifold. Imposing tadpole cancellation, N flux is bounded from the number of orientifold O3-planes. Combined with the flux quantisation, this forbids orientifold vacua without anti-brane charge. On the other hand, the presence of negative D3-brane charge induced by magnetised D7-branes breaks supersymmetry and relaxes the bound, allowing significantly smaller values for g s .